O poder judiciário e a efetividade da Lei Maria da Penha: análise da atuação do Tribunal de Justiça do Estado do Maranhão nos processos de violência psicológica contra as mulheres durante o período de 2006 a 2017 - ALENCAR, Gabriela Serra Pinto de (2019)
This research deals with the Judiciary and the effectiveness of the Maria da Penha Law, based on the analysis of the actions of the Court of Justice of the State of Maranhão in the cases of psychological violence against women during the years 2006 to 2017. Using the theoretical assumption by Pierre Bourdieu's, based on the critical analysis of the categories "official representations", "habitus" and "legal field". The techniques of research procedures are based on documentary research on the TJ MA website, through the term "domestic and family violence", delimited by the aforementioned period of time. It restricts research to one hundred and eight processes that specifically involve psychological violence. It analyzes the peculiarities of psychological violence, the role of feminist movements and the international context that allowed the emergence of the Maria da Penha Law and the recognition of psychological violence as a public and political issue. It talks about the untouchability of the private space and addresses considerations on the public and private spheres in Brazil. It points out the legal typology of psychological violence, reinforcing that it is not only restricted to the criminal aspect and covers conduct that is far beyond the crime of threat. It analyzes the social function of the Judiciary, considered as a legal field, as well as the training of magistrates in Brazil and how its reflexes in facing domestic and family violence. It comments on the judicial organization of the TJ-MA and female representation in the organ, as well as the time of judgment of the processes of psychological violence, relating it to the national context of slowness of the Judiciary Power in cases of gender violence. It analyzes the representations of the TJ MA about the women victims, and in relation to the expressions used by the judges to refer to the psychological violence. Finally, it presents the content of the decisions of the TJ MA and the tendency to maintain first-degree decisions, based on the review function of the public institution.